التحري عن قابلية البكتريا الممرضة للجهاز البولي على تكوين الغشاء الحيوي و تقييم طرق الكشف عنه - علا عبد الجليل إبراهيم (University of Thi-Qar Journal of Science, 2019)
twenty urine samples were collected from patients have acute  inflammation of the urinary tract with kidney sands . three types of bacteria were isolated from samples. it was found that the main causative agent for  85% of these conditions  due to E.coli while the remaining ones belongs to  Pseudomonas aeruginosa and Klebsiella pneumoniae. to detect the ability of these isolates to form biofilm . two different methods were used , the first  method is tube method (TM) showed that  E. coli possesses high effectiveness of  biofilm formation in the glass as well as Pseudomonas aeruginosa while the bacterium Klebsiella pneumoniae able to form biofilm moderately. It was observed when using the second method Congo red method (CRA) that all isolates composed biofilm when cultured on CRA except 5% of isolates belongs to bacterium Pseudomonas aeruginosa was negative for this test, . the first method is more accurate than the other to show the degree of biofilm formation to the naked eye, and both methods are considered qualitative not quantitative. The present study aims to investigate the ability of bacteria isolated from people with frequent urinary tract infections UTI associated with kidney stones on biofilm production .تم جمع عشرين عينة ادرار لمرضى يتكرر لديهم التهاب المجاري البولية الحاد. وقد شخص وجود ثلاث أنواع بكتيرية مسببة لهذه الحالات المرضية وكان المسبب الرئيسي ل 85% منها يعود لبكتريا E.coli وكانت عائدية المتبقي منها لكل من Pseudomonas aeruginosa و Klebsiella pneumonia .و للكشف عن قابلية هذه العزلات على تكوين ألغشاء الحيوي Biofilm تم استخدام طريقتين مختلفتين وهي طريقة tube method (TM) وقد اتضح منها ان E.coli تمتلك فعالية عالية على تكوين الغشاء الحيوي في الزجاج وكذلك بكتريا Pseudomonas aeruginosa في حين كانت قدرة بكتريا  Klebsiella pneumonia على تكوين الغشاء متوسطة. ولوحظ عند استخدام الطريقة الثانية Congo red method(CRA) ان جميع العزلات مكونة للغشاء الحيوي عند زرعها على وسط CRA وذلك بظهور مستعمرات سوداء اللون باستثناء    5% من العزلات ترجع لبكتريا Pseudomonas aeruginosa كانت سالبة لهذا الاختبار حيث ظهرت المستعمرات فيها باللون الأحمر وهذا يدل على عدم قابليتها على انتاج الغشاء الحيوي.وتبين ان الطريقة الأولى اكثر دقة من الأخرى في اظهار درجة تكون الغشاء الحيوي بالعين المجردة وان كلتا الطريقتين تعتبران طرق نوعية وليست كمية. وهدفت الدراسة للتحري عن قابلية البكتريا المعزولة من اشخاص مصابين بالتهاب المجاري البولية الحاد والمتكررUTI  والمرافق لحصى الكلية على انتاج الغشاء الحيوي (Biofilm) .